Body practices and mobile health. Reflecting on an experience with pregnant women - Delgado, Stefania Betancourt; Serapiao, Adriane Beatriz de Souza [UNESP]; Munoz, Jorge Andres Jimenez (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2024)
The present research aimed to interpret the interactions of pregnant women who participated in the Mobile health and bodily practices program within the Family Health Units in the city of Rio Claro, S & atilde;o Paulo, Brazil. The program was built based on the concepts of body practice and care, which acted as humanizing principles. Furthermore, the Ser Mamae mobile application was designed, which facilitated the implementation of this program, taking into account the possibilities of mobile health in current digital contexts. In this way, in the research, it was possible to understand that the program facilitated the recognition of wome & ntilde;s interests throughout the process, their social and health needs, as well as their emotional, physical and social dimensions. Furthermore, the creation of a support network promoted scenarios of body self-recognition and the improvement of health care in terms of promoting healthy practices, monitoring the gestational process and care actions. Finally, we argue the contribution that the concepts of body practice and care have in re-signifying the theoretical framework of professionals in the field of Physical Education in interface with health and mobile health.
Keywords: Mobile health; Pregnant women; Body practices; Careful